Fruit quality and shelf-life improvement of tomato (Solanum lycopersicum L.) 'Servo' by inorganic fertilizer enriched with amino acid - Zalfa Amelia; Murti, Rudi Hari; Ilmiah , Haviah Hafidhotul; Purwanto, Benito Heru (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
Fertilizer and maturity stage affect the nutritional content and quality of tomatoes. This study aimed to obtain the best dosage of amino acid fertilizer on the qualities and shelf life and to determine the effect of the maturity stage on the qualities of Servo tomatoes. The research design used factorial RCBD with 3 blocks as replications. The Servo tomatoes were grown in Wonosobo District and foliar fertilized with 4 levels of amino acid fertilizer, namely 0, 1, 2, and 4 L ha-1 amino acid fertilizer, and 2 L ha-1 comparison fertilizer. Observation of tomato fruit quality was conducted in Horticulture Sublaboratory, UGM at 27,5 °C with relative humidity of 73%. The quality observed was CO2 concentration, visual quality rating, weight loss, fruit firmness, fruit color, TSS, TTA, carotenoids, lycopene, flavonoids, and vitamin C. The observation was terminated when the score of VQR reached 3 as shelf life of tomatoes. Amino acid fertilizer can improve the quality of Servo tomatoes as seen from the parameters of fruit color (a*) and total titrated acid (TTA). In terms of other parameters, the amino acid fertilizer does not affect the quality of Servo tomatoes. The highest value on fruit color (a*) and TTA resulted from 2 L ha-1 of amino acid fertilizer. The maturity stage significantly affects the quality improvement of fruit firmness, weight loss, VQR, CO2 concentration, TTA, total soluble solids, carotenoids, and flavonoids. L ha-1 Keywords: Aminoalkanoic; fertilizer effect; storage life; tomato quality